Primaquine ineligibility in anti-relapse therapy of Plasmodium vivax malaria: the problem of G6PD deficiency and cytochrome P-450 2D6 polymorphisms - Baird, J. Kevin (Malar J, 2018)
The hypnozoite reservoir of Plasmodium vivax represents both the greatest obstacle and opportunity for ultimately eradicating this species. It is silent and cannot be diagnosed until it awakens and provokes a clinical attack with attendant morbidity, risk of mortality, and opportunities for onward transmission. The only licensed drug that kills hypnozoites is primaquine, which attacks the hypnozoite reservoir but imposes serious obstacles in doing so—at hypnozoitocidal doses, it invariably causes a threatening acute haemolytic anaemia in patients having an inborn deficiency in glucose-6-phosphate dehydrogenase (G6PD), affecting about 8% of people living in malaria endemic nations. That problem excludes a large number of people from safe and effective treatment of the latent stage of vivax malaria: the G6PD deficient, pregnant or lactating women, and young infants. These groups were estimated to comprise 14.3% of populations resident in the 95 countries with endemic vivax malaria. Another important obstacle regarding primaquine in the business of killing hypnozoites is its apparent metabolism to an active metabolite exclusively via cytochrome P-450 isozyme 2D6 (CYP2D6). Natural polymorphisms of this allele create genotypes expressing impaired enzymes that occur in over 20% of people living in Southeast Asia, where more than half of P. vivax infections occur globally. Taken together, the estimated frequencies of these primaquine ineligibles due to G6PD toxicity or impaired CYP2D6 activity composed over 35% of the populations at risk of vivax malaria. Much more detailed work is needed to refine these estimates, derive probabilities of error for them, and improve their ethnographic granularity in order to inform control and elimination strategy and tactics.